(untitled) (Research, Society and Development, 2021)
In the current COVID-19 pandemic, social isolation persists, with recurrent outbreaks and a number of chaos in several countries. With this isolation, elderly people who are more likely to report loneliness are more likely to develop depression and psychological distress. To reduce these damages, physical activity can be beneficial in this population in relation to mental health. From this perspective, the objective was to analyze the contributions of physical exercise to the mental health of the elderly during the COVID-19 pandemic. A systematic review was carried out in the Virtual Health Library, ScienceDirect and Pubmed databases. In which articles were included that had intervention with a control group of physical exercise in the elderly with variables in mental health during the COVID-19 pandemic. After the search, 9 articles were selected. Studies show different exercises can improve mental health by decreasing perceived stress, symptoms of depression, cognitive stimulation, socio-psychological prosperity and increasing mental quality of life. This systematic review shows that physical exercise can contribute to the mental health of elderly people in the COVID-19 pandemic. Future studies are needed with larger samples and in different populations.